Accuracy of Cardiovascular Trial Outcome Ascertainment and Treatment Effect Estimates from Routine Health Data: A Systematic Review and Meta-Analysis. Issue 5 (17th May 2021) - Rodrigues, Craig; Odutayo, Ayodele; Patel, Sagar; Agarwal, Arnav; da Costa, Bruno Roza; Lin, Ethan; Yeh, Robert W.; Jüni, Peter; Goodman, Shaun G.; Farkouh, Michael E.; Udell, Jacob A.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Registry-based randomized controlled trials allow for outcome ascertainment using routine health data (RHD). While this method provides a potential solution to the rising cost and complexity of clinical trials, comparative analyses of outcome ascertainment by clinical end point committee (CEC) adjudication compared with RHD sources are sparse. Among cardiovascular trials, we set out to systematically compare the incidence of cardiovascular events and estimated randomized treatment effects ascertained from RHD versus traditional clinical evaluation and adjudication. Methods: We searched MEDLINE (1976 to August 2020) for studies where outcome ascertainment was performed by both RHD and CEC adjudication to compare the incidence of cardiovascular events and treatment effects. We derived ratios of hazard ratios to compare treatment effects from RHD and CEC adjudication. We pooled ratios of hazard ratios using an inverse variance random-effects meta-analysis. Results: Nine studies (1988–2020; 32 156 patients) involving 10 randomized control trials compared outcome ascertainment with RHD and CEC in patients with or at risk of cardiovascular disease. There was a high degree of agreement and interrater reliability between CEC and RHD outcome determination for all-cause mortality (agreement percentage: 98.4%–100% and κ: 0.95–1.0) and cardiovascular mortality (agreement percentage: 97.8%–99.9% and κ: 0.66–0.99). For myocardial infarction, the κ values ranged from 0.67–0.98, and for stroke the values ranged from 0.52–0.89. In contrast, the κ value for peripheral artery disease was low (κ: 0.27). There was little difference in the randomized treatment effect derived from CEC and RHD ascertainment of events based on the ratios of hazard ratio, with pooled ratios of hazard ratios ranging from 0.93 (95% CI, 0.63–1.39) for cardiovascular mortality to 1.27 (95% CI, 0.67–2.41) for stroke. Conclusions: Clinical outcome ascertainment using retrospectively acquired RHD displayed high levels of agreement with CEC adjudication for identifying all-cause mortality and cardiovascular outcomes. Importantly, cardiovascular treatment effects in randomized control trials determined from RHD and CEC resulted in similar point estimates. Overall, our review supports the use of RHD as a potential alternative source for clinical outcome ascertainment in cardiovascular trials. Validation studies with prospectively planned linkage are warranted.